Capacitors: Block‐Copolymer‐Assisted One‐Pot Synthesis of Ordered Mesoporous WO3−x/Carbon Nanocomposites as High‐Rate‐Performance Electrodes for Pseudocapacitors (Adv. Funct. Mater. 30/2013). (8th August 2013) - Jo, Changshin; Hwang, Jongkook; Song, Hannah; Dao, Anh Ha; Kim, Yong‐Tae; Lee, Sang Hyup; Hong, Seok Won; Yoon, Songhun; Lee, Jinwoo
<x xml:space="preserve">Abstract</x> A study by S. Yoon, J. Lee, and co‐workers on the improvement of rate performance highlights an important issue for pseudocapacitor electrode materials. On page 3747, the synthesis of an ordered mesoporous tungsten oxide–carbon nanocomposite is presented via a 'one‐pot' soft‐template method. The ordered mesoporous structure, partial reduction of the metal oxide, and the nanosized mixing of the metal oxide/carbon result in both high power and energy density. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>